2016
DOI: 10.1007/s11239-016-1354-3
|View full text |Cite
|
Sign up to set email alerts
|

Superficial vein thrombosis treated for 45 days with rivaroxaban versus fondaparinux: rationale and design of the SURPRISE trial

Abstract: Patients with superficial vein thrombosis (SVT) are commonly treated with low-molecular weight heparin or fondaparinux in prophylactic, intermediate or therapeutic dosages for treatment periods of 10-45 days. This practice is also reflected by the current guideline recommendations. However, given the broad range of thromboembolic complication rates in SVT (between 0 and 30 % have been reported) it seems reasonable to suspect that risk stratification is needed to differentiate patients at low risk who may not b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 18 publications
0
8
0
2
Order By: Relevance
“…Overall rates of symptomatic recurrent VTE (SVT, DVT, or PE) at three months were 8.3% (6.0 e 10.6) in POST, 3.0% (1.7 e 4.9) in OPTIMEV, 3.3% (2.1 e 4.8) and 5.5% (2.3 e 11.0) in the fondaparinux or heparin treated patient groups in PERSEUS, respectively. Furthermore, two randomised clinical trials, CALISTO 7 and SURPRISE, 14 are lined up to investigate the use of the pentasaccharide fondaparinux, or to compare fondaparinux with the DOAC rivaroxaban in the treatment of SVT patients with a "high" thromboembolic risk, respectively. As a learning from former randomised clinical evidence 15,16 these two studies implemented a longer treatment duration of six weeks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall rates of symptomatic recurrent VTE (SVT, DVT, or PE) at three months were 8.3% (6.0 e 10.6) in POST, 3.0% (1.7 e 4.9) in OPTIMEV, 3.3% (2.1 e 4.8) and 5.5% (2.3 e 11.0) in the fondaparinux or heparin treated patient groups in PERSEUS, respectively. Furthermore, two randomised clinical trials, CALISTO 7 and SURPRISE, 14 are lined up to investigate the use of the pentasaccharide fondaparinux, or to compare fondaparinux with the DOAC rivaroxaban in the treatment of SVT patients with a "high" thromboembolic risk, respectively. As a learning from former randomised clinical evidence 15,16 these two studies implemented a longer treatment duration of six weeks.…”
Section: Discussionmentioning
confidence: 99%
“…SURPRISE was a randomised noninferiority study, that enrolled a higher risk profile population and showed a non-significant trend toward higher rate of primary outcome, concluding a non-inferiority of rivaroxaban to fondaparinux. 14,15 The CALISTO results were subsequently implemented in various international guidelines recommending fondaparinux, to be preferred over other treatment options (according to the European Society for Vascular Surgery [ESVS] 2021 guidelines, an intermediate dose of a low molecular weight heparin should be considered as an alternative to fondaparinux). 17e19 As shown in PERSEUS and INSIGHTS-SVT, fondaparinux evolved as a preferred treatment option, with shares of 75.2% and 65.7% of patients receiving this drug, showing LMWH as second choice.…”
Section: Discussionmentioning
confidence: 99%
“…In der SURPRISE-Studie von 2016 wurden 472 Patienten mit OVT und einem weiteren Risikofaktor für thromboembolische Komplikationen (Alter > 65 Jahre; männliches Geschlecht; frühere OVT, TVT oder Lungenembolie; akute oder frühere Krebserkrankung; Autoimmunerkrankung; Thrombose in nichtvarikösen Venen) randomisiert und erhielten Rivaroxaban 10 mg p. o. 1-mal täglich oder Fondaparinux 2,5 mg s. c. 1-mal täglich über 45 Tage in beiden Gruppen [33,34]. Die Studie war als offene "Nichtunterlegenheitsstudie" konzipiert worden.…”
Section: Direkte Orale Antikoagulanzien (Doak) -Rivaroxabanunclassified
“…The majority of studies that compared different oral treatment, topical treatment, or surgery did not report VTE, SVT progression, adverse events, or treatment side effects. The authors concluded that further research is needed to evaluate whether a combination of different interventions is superior to single interventions, which is also indicated by the fact that~10% of the study population in the Superficial Phlebitis Treated for 45 Days with Rivaroxaban Versus Fondaparinux (SURPRISE) trial 26,27 received short courses of NSAID therapy in addition to anticoagulant therapy despite a lack of evidence for such a combination, which may increase bleeding risk.…”
Section: Evidence For Nonanticoagulant Treatment Options In Svtmentioning
confidence: 99%
“…The prospective randomized SURPRISE trial compared 10 mg rivaroxaban orally vs 2.5 mg fondaparinux subcutaneously over 45 days in selected high-risk patients with above-knee SVT who had additional risk factors for thromboembolic complications, such as male sex, history of DVT/PE, previous or active cancer, systemic inflammatory disease, or SVT in nonvaricose veins. 26,27 In the 435 patients included in the per-protocol analysis, thromboembolic complications occurred at day 45 in 3% and 2% of patients in the rivaroxaban and fondaparinux groups, respectively. There were no major bleeds in either group.…”
Section: Evidence For Anticoagulant Treatment In Svtmentioning
confidence: 99%